2022
DOI: 10.1155/2022/4882521
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study and Improvement Analysis of Sparrow Search Algorithm

Abstract: To solve the problem that the emerging sparrow search algorithm (SSA) lacks systematic comparison and analysis with other classical algorithms, this paper first introduces the principle of the sparrow search algorithm and then describes the mathematical model and algorithm description of the sparrow search algorithm. By comparing several classical intelligent algorithms with particle swarm optimization (PSO), differential evolution (DE), and gray wolf optimizer (GWO), the sparrow search algorithm’s theory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The SSA is a nascent optimization algorithm rooted in swarm intelligence principles [ 34 ] that learns from the behavioral strategies of sparrows, including foraging and anti-predation. The authors of [ 35 ] compared the performance of four emerging intelligent optimization algorithms: Grey Wolf optimization (GWO), particle swarm optimization (PSO), the differential evolution (DE) algorithm, and the SSA. Their experimental results indicated that the SSA exhibits strong local search ability under a variety of test function experiments, and has the advantages of high precision and fast convergence speed.…”
Section: Algorithm Principlesmentioning
confidence: 99%
“…The SSA is a nascent optimization algorithm rooted in swarm intelligence principles [ 34 ] that learns from the behavioral strategies of sparrows, including foraging and anti-predation. The authors of [ 35 ] compared the performance of four emerging intelligent optimization algorithms: Grey Wolf optimization (GWO), particle swarm optimization (PSO), the differential evolution (DE) algorithm, and the SSA. Their experimental results indicated that the SSA exhibits strong local search ability under a variety of test function experiments, and has the advantages of high precision and fast convergence speed.…”
Section: Algorithm Principlesmentioning
confidence: 99%
“…Using ( 2) or ( 12) to update the scroungers' position; (10) end for (11) for i � 1: SD do (12) Using equation ( 3) to update the scouters' position; (13) end for (14) for i � 1: N do (15) if the new position is better than the previous position then (16) Using the new position to update the previous position; (17) end if (18) if the new position is better than the optimal position then (19) Using the new position to update the optimal position; (20) end if (21) end for (22) t � t + 1 (23) end while (24) return f best , X best ALGORITHM 1: Te improved sparrow search algorithm. Computational Intelligence and Neuroscience Equation ( 13) can be expressed as a matrix as follows:…”
Section: Inputmentioning
confidence: 99%
“…Compared with other algorithms, SSA has some advantages in convergence speed and global search ability. Nevertheless, when solving complex problems, the performance of SSA is greatly afected by the initial population, and the diversity of the population will decrease signifcantly with the iterative process [17]. In addition, in the optimization process, the convergence accuracy of SSA needs to be improved, and the ability to jump out of the local optimal solution needs to be enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…The sparrow search algorithm (Yan, et al, 2022) is a new intelligent algorithm that imitates sparrow foraging and predation. In the SSA algorithm, the discoverer, joiner and scout cooperate to carry out local search and global search.…”
Section: Sparrow Search Algorithmmentioning
confidence: 99%